Advancements in the in vitro culture of human pluripotent stem cells: progress, challenges, and future directions: comprehensive review - Chaudhary, Niraj; Villa-Diaz, Luis G. (Frontiers in Toxicology, 2025)
The advancement of human pluripotent stem cell (hPSC) culture systems has revolutionized the landscape of preclinical drug discovery and toxicological evaluation. Progressing innovations from feeder-dependent and xenogeneic matrices to chemically defined, xeno-free, and fully synthetic platforms have addressed long-standing challenges in reproducibility, safety, and clinical translation. Developments in recombinant extracellular matrix proteins, synthetic peptide substrates, and polymer-based coatings have enabled the generation of Good Manufacturing Practice (GMP)-compliant, scalable hPSC cultures while minimizing biological variability and immunogenic risks. Integration of automation, artificial intelligence (AI), and three-dimensional (3D) bioprocessing technologies aims at further enhancement of standardization, quality control, and throughput. In the context of pharmaceutical research, hPSC-derived cellular models now underpin high-throughput drug screening and mechanistic toxicological assays, offering superior human relevance compared to traditional animal models. Despite these advances, barriers such as cellular immaturity, inter-batch variability, and limited regulatory acceptance persist, underscoring the need for further protocol standardization and technological refinement. This review provides a comprehensive analysis of current animal-free hPSC culture platforms, critically examines their strengths and limitations, and discusses future directions for advancing their application in drug discovery and predictive toxicology. The ongoing evolution of hPSC technologies promises to accelerate the development of safer, more effective therapeutic agents and to reshape the future of human disease modeling and pharmacological research.